Designing a Legal Framework of Green Environment in Smart Home Project - Asmah Laili Yeon; Noor Ashikin Basarudin; Zuryati Mohamed Yusof; Nuarrual Hilal Md Dahlan; Nazli Mahdzir (International Journal of Supply Chain Management, 2018)
Smart home concept in Malaysia is still in the early stage. There is no comprehensive and specific law and rules which governs the smart home project. The installation of smart home gadgets and facilities is on the choice of the home proprietors themselves. The question arise is to what extend the law and policy in Malaysia can accommodate the development of smart home project which gives priority to preserve green environment. Therefore, the objective of the paper is to highlights amendments to the law and policy in ensuring the success of the smart home project and preservation of green environment. This paper is based on a legal doctrinal research and qualitative research. Mixed method was used in analysing the data. Legal doctrinal analysis was performed based on the statutory provisions of housing statutes, codes, and guidelines. Qualitative data were collected by way of interview with 13 experts of smart home and green environment. It is suggested that the Government of Malaysia to recognise the environmental potential of smart features, to commission and support research in establishing a robust evidence base. Some amendments to the existing law and new policy of smart home and green technology should be established to support both agenda.